PENGARUH TEKNIK REINFORCEMENT TERHADAP HASIL BELAJAR BIOLOGI POKOK BAHASAN SISTEM PEREDARAN DARAH MANUSIA - Andi Makkawari Latif; Muchlisah Muchlisah; Eka Damayanti (Jurnal Biotek, 2017)
This thesis discusses the influence of reinforcement technique on student learning outcomes that aims to know (1) description of biology learning result of students of grade XI IPA of SMA Negeri 16 Makassar taught by applying reinforcement technique; (2) description of biology learning result of grade XI IPA student of SMA Negeri 16 Makassar taught without applying reinforcement technique and (3) influence of reinforcement technique toward biology student learning result of class XI IPA SMA 16  Makassar. This research is kind of Quasi Experimental Reserch research with Pretest-Postest Control Group Design Design research. The population of this study is all students of class XI IPA SMA Negeri 16 Makassar, amounting to 252 students consisting of class XI IPA1 up to XI IPA7. The sample in this research is class XI IPA4 as control class which amounted to 36 people and student class XI IPA7 as experiment class which amounted to 36 people. Data analysis technique used in this research is descriptive analysis and inferential analysis. The results of descriptive analysis of learning outcomes for the control class has an average value of 54.28. While the results of descriptive analysis of experimental class learning results have an average value of 75.17. Based on the classification of student learning outcomes, the average value of the control class is in the range of values 40-54 with low category whereas the average value of the experimental class is in the range of values of 75-89 with high category. Based on the result of hypothesis analysis by using t-test polled variance, tcount> ttable (10,631> 1,690) so Ho is rejected and H1 accepted. This means that there is influence of reinforcement techniques on student biology learning outcomes.